Anti-Corruption in International Development - Kerusauskaite, Ingrida (London : Taylor and Francis, 2018)
"Corruption is linked to a wide range of developmental issues, including undermining democratic institutions, slowing economic development and contributing to government instability, poverty and inequality. It is estimated that corruption costs more than 5 per cent of global GDP, and that more than one trillion US dollars are paid in bribes each year. This book unpacks the concept of corruption, its political and ethical influences, its measurement, commitments to combat corruption and ways that this is being attempted.Building on the research on the nature, causes and consequences of corruption, this book analyses international anti-corruption interventions in particular. It discusses approaches to focus efforts to tackle corruption in developing countries on where they are most likely to be successful. The efforts of the UK are considered as a detailed case study, with comparisons brought in as necessary from other countries and multilateral institutions anti-corruption efforts. Bridging a range of disciplines, Anti-Corruption in International Development will be of interest to students and scholars of international development, public administration, management, international relations, politics and criminal justice."--Provided by publisher.
chapter 1 Introduction -- chapter 2 Conceptual framework: definitions and the nature of corruption -- chapter 3 Theoretical approach to anti- corruption interventions in international development -- chapter 4 The UK$1 (Bs anti- corruption work in developing countries -- chapter 5 International law and development: where anti- corruption interventions fit in -- chapter 6 The UK government$1 (Bs use of multilateral and bilateral approaches to tackle corruption in developing countries -- chapter 7 Conclusions and wider implications.s
Keywords: Crime prevention; Crime; Economic development -- Study and teaching; African & Third World Politics; Crime and Crime Prevention; Development Studies; Africa -- Politics and government; Developing countries -- Politics and government